Marjory Wardrop and Guria - Anthony Stobart (The Kartvelologist - A Bilingual Peer-reviewed, Academic Journal of Georgian Studies, 2018)
This article summarizes the travels of marjory Wardrop in Guria during her first visit to Georgia in 1894-1895 with reference to material in the wardroom collection in the Boolean Library